1951
DOI: 10.1182/blood.v6.11.1159.1159
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Iron: Evaluation of the Use of Saccharated Iron Oxide in Iron Deficiency States in Obstetrics and Gynecology

Abstract: Saccharated iron oxide has been given to 23 patients in doses of 480 to 1,430 mg. Toxic symptoms were minimal. Hematologic response was good in 21 patients. Continued bleeding accounted for the poor response in 2 persons. Saccharated iron oxide is a safe preparation for clinical use. It is easy to administer. Further clinical evaluation is warranted. Excessive amounts of intravenous iron should not be given to any individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1952
1952
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…iron to treat IDA in pregnant women was first examined almost 60 years ago; enhanced Hb levels following i.v. iron sucrose administration were demonstrated while iron not utilized by the hematopoietic tissues helped replenish maternal iron stores [17]. More recent studies have demonstrated i.v.…”
Section: IV Ironmentioning
confidence: 99%
“…iron to treat IDA in pregnant women was first examined almost 60 years ago; enhanced Hb levels following i.v. iron sucrose administration were demonstrated while iron not utilized by the hematopoietic tissues helped replenish maternal iron stores [17]. More recent studies have demonstrated i.v.…”
Section: IV Ironmentioning
confidence: 99%